Activated sugarcane bagasse ash as efficient admixture in cement-based mortars: Mechanical and durability improvements. (1st November 2022) - Torres de Sande, Veronica; Sadique, Monower; Bras, Ana; Pineda, Paloma
Abstract: Biomass ashes can be used in cementitious materials as cement or sand substitution. Nevertheless, ashes resulted from the combustion of biomass in generation plants present drawbacks that can reduce their potential use if they are not previously treated. In this research, industrial sugarcane bagasse ash (SCBA) was mechanically activated by grinding and its effects evaluated when used as mineral admixture in cementitious materials. Four different substitution rates (0%, 10%, 20% and 30%) where used to investigate the influence of the amount of ashes replaced on the durability and mechanical performance of mortars and identify the optimal substitution rate. To get a thorough comprehension, results were also compared to mortars containing untreated ashes. The combination of a performance-based testing campaign (compressive and flexural strength, open porosity, apparent density, water capillary absorption, surface electrical resistivity, rapid chloride migration coefficient) and a set of analytical techniques (XRD, FT-IR, SEM and TGA-DTA) enabled to characterise the mechanical and durability properties of mortars and identify the mechanisms behind the results. The research concluded that, at 28 days, the incorporation of ground SCBA enhances the compressive strength of mortars up to 62%, decreases the porosity of samples by 35%, highly improves the resistance to the diffusion of chlorides by 10 times and improve the interfacial transition zone by narrowing and closing the gap between aggregates and pastes. Highlights: SCBA containing <70% of main oxides used as mineral admixture. Grinding reduces the drawbacks of using untreated ashes. Combination of performance-based tests and analytical methods. Mechanical and durability properties remarkably enhanced. Mechanisms behind the improved performance of mortars are identified.